2014
DOI: 10.1007/s12519-014-0522-9
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic factors related to double-bar insertion in minimal invasive repair of pectus excavatum

Abstract: CT scan provides useful factors which can be of assistance in predicting the number of pectus bars for the surgical correction of pectus excavatum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…A previous study confirmed that miR-182 activates the PI3K/AKT pathway (31), whereas CADM3 inhibits activation of the PI3K/AKT signaling pathway, and CADM3 can bind to CADM4 (32). Non-overlapping expression of CADM2 and CADM3 has been detected in the developing retina, and binding of CADM2 and CADM3 to CADM1 and CADM4 in vitro may indicate the functional role of CADMs during nervous system development (33). VEGF is an angiogenic growth factor that is involved in the pathogenesis of retinal diseases, such as diabetic retinopathy (34).…”
Section: Discussionsupporting
confidence: 55%
“…A previous study confirmed that miR-182 activates the PI3K/AKT pathway (31), whereas CADM3 inhibits activation of the PI3K/AKT signaling pathway, and CADM3 can bind to CADM4 (32). Non-overlapping expression of CADM2 and CADM3 has been detected in the developing retina, and binding of CADM2 and CADM3 to CADM1 and CADM4 in vitro may indicate the functional role of CADMs during nervous system development (33). VEGF is an angiogenic growth factor that is involved in the pathogenesis of retinal diseases, such as diabetic retinopathy (34).…”
Section: Discussionsupporting
confidence: 55%